2020
DOI: 10.31234/osf.io/tdaqg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding the (most efficient) way out of a maze is easier than asking (good) questions.

Abstract: We investigate whether a spatial representation of a search task supports 4- to 7-year-old children’s information-search strategies, relative to their performance in a question-asking game. In Experiment 1, children played two computationally and structurally analogous search games: a spatial search task, the maze-exploration game, in which they had to discover the path through a maze, and a verbal search task, the 20-questions game, where they had to identify a target monster from a set of eight monsters by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…In addition, we wanted to investigate to what extent TÖRÖK, SWABODA, AND RUGGERI 10 children's difficulties in Experiment 1 were task-specific, that is, related to the question-asking paradigm we used. We therefore also presented children with a spatial search game (maze-exploration game, adapted from Swaboda et al, 2021), in which agents did not make queries by asking questions, but by looking under a set of cards concealing the passages of a two-dimensional maze. This task was designed such that the strategies (3CS vs. 3HS) were equivalent in efficiency and effectiveness to the strategies in the 20-questions game.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we wanted to investigate to what extent TÖRÖK, SWABODA, AND RUGGERI 10 children's difficulties in Experiment 1 were task-specific, that is, related to the question-asking paradigm we used. We therefore also presented children with a spatial search game (maze-exploration game, adapted from Swaboda et al, 2021), in which agents did not make queries by asking questions, but by looking under a set of cards concealing the passages of a two-dimensional maze. This task was designed such that the strategies (3CS vs. 3HS) were equivalent in efficiency and effectiveness to the strategies in the 20-questions game.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…What's more, recent work shows that in nonverbal tasks that do not involve question-asking at all, children are able to implement efficient search strategies themselves much earlier. For example, Swaboda et al (2021) showed that 4-year-olds searched as efficiently as 7-year-olds in a spatial search task, where they had to find the path through a partially blocked maze by uncovering its concealed passages (Swaboda et al, 2021). In another study, children (ages 3 to 5 years) searched for an egg shaker hidden in one of two boxes after learning that it was either always hidden in the same box, or in a different box.…”
Section: Children's Sensitivity To the Efficiency Of Question-asking ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Permainan ini dibuat dengan menggunakan maze sehingga anak-anak harus melewati maze tersebut dengan berbagai tantangan yang ada. Menurut (Swaboda, Meder, & Ruggeri, 2020) mengatakan bahwa kemampuan anak secara fleksibel dapat menggolongkan suatu objek berdasarkan fitur alternatif untuk memprediksi seberapa besar anak memainkan permainan. Berdasarkan beberapa pendapat tersebut, maka permainan dapat didefinisikan sebagai usaha keterampilan pengetahuan pada permainan maze untuk menemukan jalan keluar yang tersulit agar mencapai tujuan yang dicapainya.…”
Section: Pendahuluanunclassified